Characteristics of Pyrolysis and Copyrolysis Products Sewage Sludge in Different Temperature Ranges - Yunbing Li; Hongli Li; Qihang Zhang; Xinyi Wang; Xin Wang; Pen Jin (Journal of Chemistry)
Rapid modernization, population growth, and improvement in people’s quality of life have resulted in an increase in urban sewage sludge as the main solid waste. At present, pyrolysis is the main treatment method for sludge due to carbon-free effects and less air pollution compared with incineration. To enhance the energy utilization value of sludge, copyrolysis of sludge and biomass with varying effects has been reported. Herein, biomass and sludge were pyrolyzed and copyrolyzed using self-designed fixed-bed pyrolysis and condensation collection system. The pre-fixed-bed process parameters were optimized by orthogonal test, and it was found that the carrier gas flow rate (a) > bed thickness (b) > constant temperature time (c). The optimum process combinations were 250 mL/min carrier gas, 10 mm bed thickness, and 10 min constant temperature. Experiments show that the ultimate pyrolysis temperature affects the oil production of fixed-bed pyrolysis by up to 15%. Copyrolyzing Sargassum thunbergii and sludge boost oil output at first and then drops; the maximum value is at 20% sludge. When pine sawdust and sludge were copyrolyzed, oil output climbed marginally and subsequently fell fast; the highest value was at 20% sludge. Peanut shell and sludge copyrolysis yield the most oil at 40% sludge content, and the experimental value is smaller than the linear value at 80% sludge content.